Gender Differences in Cardiovascular Drugs - Stolarz, Amanda J.; Rusch, Nancy J. (Cardiovascular drugs and therapy, 2015)
The different responses of women and men to cardiovascular drugs reflect gender –specific variances in pharmacokinetic profiles and drug sensitivities coupled to inherent differences in the underlying physiology of each sex. Thus, many common cardiovascular drugs exhibit gender -specific therapeutic and adverse effects. For example, the QT interval of the electrocardiogram is longer in women compared to men, and accordingly, drugs that prolong the QT interval are more likely to cause lethal ventricular arrhythmias in female than male patients. As more clinical drug trials include women subjects, our improved knowledge base for assessing the risk/benefit ratio for cardiovascular drugs in women will enable us to consider gender as one factor in prescribing drugs and adjusting drug loading and maintenance dosages. This short review will present evidence for gender- related differences in the responses to common cardiovascular drugs including statins, antiplatelet and antithrombotic agents, β-blockers, digoxin, vasodilator therapies, and drugs associated with the Long QT Syndrome.